The Effect of Language on Economic Behavior: Experimental Evidence from Children's Intertemporal Choices - Matthias Sutter; Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer (Institute for the Study of Labor (IZA), 2015)
According to Chen's (2013) linguistic-savings hypothesis, languages which grammatically separate the future and the present (like English or Italian) induce less future-oriented behavior than languages in which speakers can refer to the future by using present tense (like German). We complement Chen's approach with experimentally elicited time preference data from a bilingual city in Northern Italy. We find that German-speaking primary school children are about 46% more likely than Italian-speaking children to delay gratification in an intertemporal choice experiment. The difference remains significant in several robustness checks and when controlling for a broad range of factors, including risk attitudes, IQ or family background.
Keywords: C91; D03; D90; 330; intertemporal choice; language; children; experiment